Correctional Facilities and Correctional Treatment (IntechOpen, 2023)
This book provides international perspectives on corrections, correctional treatment, and penitentiary laws. Although its focus is on African and South American countries, the information provided can be easily expanded to North America and Europe. The chapters present legal frameworks and applied research on prisons and their potential to deter crime and reduce recidivism rates. The book puts the human rights agenda at the forefront and is a useful resource for those who work in corrections, including prison, education, and probation officers.